Diagnostic and prognostic contribution of 99mTc-DPD scintigraphy in transthyretin V30M cardiac amyloidosis. (14th October 2021) - Azevedo Coutinho, M D C; Cortez-Dias, N; Cantinho, G; Goncalves, S; Cunha, N; Rodrigues, T; Santos, L; Conceicao, I; Pinto, F
Abstract: Background: Early diagnosis and prognostic stratification of hereditary transthyretin amyloidosis (ATTR) are crucial. Previous findings suggested that 99mTc-3, 3-diphosphono-1, 2-propanodicarboxylic acid (DPD) scintigraphy presents suboptimal accuracy to detect ATTR cardiomyopathy caused by V30M mutation, particularly in patients with onset of symptoms under 50 years of age. Furthermore, its prognostic value has never been evaluated in ATTR caused by this mutation. Purpose: To assess the diagnostic value of DPD scintigraphy to detect cardiomyopathy in a large cohort of patients with ATTR-V30M mutation and to explore its prognostic value regarding mortality. Methods: Of the 305 ATTR-V30M mutation carriers followed prospectively and who underwent DPD scintigraphy, 288 individuals [median age 46 (39–56); 49% male] without myocardial thickening attributable to other causes were enrolled in the study. Amyloid cardiomyopathy was defined by septal thickness ≥13mm not attributable to other causes plus at least one of the following criteria: (1) late heart-to-mediastinum (H/M) 123I-metaiodobenzylguanidine (MIBG) ratio <1.60; (2) electrical heart disease (arrhythmia or cardiac conduction defect); or (3) amyloid infiltration documented in biopsy. Results: Amyloid cardiomyopathy was identified in 41 (14.2%) patients and 44 (15.3%) individuals presented abnormal cardiac DPD uptake. Individuals with cardiac DPD retention had 27-fold higher likelihood of having amyloid cardiomyopathy (OR: 27.4; 95% CI 11.6–65.0; P<0.001). However, DPD scintigraphy presented suboptimal accuracy to detect ATTR cardiomyopathy (89.9%) with limitations in sensitivity (56.1%), specificity (95.6%), positive predictive value (67.7%) and negative predictive value (92.9%). During a mean follow-up 33.6±1.2 months, 16 patients died (5.6%). Mortality was 14 times higher in patients with amyloid cardiomyopathy (HR: 14.1; 95% CI 4.9–40.7; P<0.001), 13 times higher in those with abnormal cardiac DPD uptake (HR: 12.59; 95% CI % 4.56–34.72; P<0.001) and 10 times higher in those with H/M MIBG ratio <1.60 (HR: 10.40; 95% CI 2.95–36.69; P<0.001). The prognostic value of ventricular thickness and cardiac DPD uptake was additive: patients without septal thickening and no cardiac DPD retention had excellent prognosis (5-year mortality of 0.75%), while those with septal thickening and/or abnormal DPD retention presented 5-year mortality rates ranging from 39.9 to 53.3%. Conclusions: DPD scintigraphy is valuable in the evaluation of ATTR-V30M mutation carriers, particularly for prognostic stratification purposes, identifying patients at higher risk of death. Funding Acknowledgement: Type of funding sources: None.